1997
DOI: 10.1038/nbt0797-658
|View full text |Cite
|
Sign up to set email alerts
|

Structure-based design and protein engineering of intersubunit disulfide bonds in gonadotropins

Abstract: Pairs of cystine residues were introduced in the alpha- and beta-subunits of human choriogonadotropin at positions with optimal geometries for the formation of disulfide bonds. Using the homology with luteinizing hormone and follicle stimulating hormone, similar mutations were carried out in these glycoprotein hormones. In nearly all mutants the corresponding disulfide bonds were formed leading to a non-natural, covalent linkage between the alpha- and beta-subunits. The mutants typically display wild-type rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

1998
1998
2008
2008

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 26 publications
2
29
0
Order By: Relevance
“…Unfortunately, our disulfide approach was not successful. Intermolecular disulfide bonds artificially introduced at positions where natural disulfides are present in homologous proteins (23), including a bacteriophage capsid (3), proved stabilizing in several cases. However, most protein oligomers, including the FMDV capsid, have no adequate disulfide-bonded homologs.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, our disulfide approach was not successful. Intermolecular disulfide bonds artificially introduced at positions where natural disulfides are present in homologous proteins (23), including a bacteriophage capsid (3), proved stabilizing in several cases. However, most protein oligomers, including the FMDV capsid, have no adequate disulfide-bonded homologs.…”
Section: Discussionmentioning
confidence: 99%
“…Purification of hCG from Dictyostelium was performed with the aid of a programmable FPLC system (Pharmacia) using the control and chromatography supervision system UNICORN (Pharmacia). Purification of single-chain hCG was accomplished using a combination of hydrophobic interaction and immuno chromatography with LH/CG β subunit-specific monoclonal antibodies (optimised protocol for hCG produced by CHO cells, see [9]). For this purpose, 150 ml medium were produced with a single-chain hCG content of 0.372 unit/ml as determined by DELFIA ® .…”
Section: Oligonucleotidementioning
confidence: 99%
“…To overcome this problem, we and others have produced mutants in which the coding regions of the hCG β subunit and the common A subunit are connected via peptide spacers [8] or intersubunit disulphide bonds [9]. It has been shown that these covalently linked A and β subunits of hCG are able to fold into biologically active conformations.…”
mentioning
confidence: 99%
“…This amount is produced in 4-5 days in a petri dish with ϳ10 6 cells per ml of medium. For comparison, the expression level of wt hCG in CHO cells is 800mU/10 6 cells per 24 h (22).…”
Section: Gonadotropin Expression In Dictyosteliummentioning
confidence: 99%
“…Concentrations of wild-type and mutant hCG were measured using a DELFIA hLH assay (Wallac Oy, Turku, Finland), which has a 100% cross-reactivity with hCG, as described by the manufacturer. FSH was quantified by a sandwich immunoassay as described previously (22). Both assays are based on the enzyme-linked immunoassay principle, with a solid-phase anti-␤ chain antibody and a soluble anti-␣ chain antibody.…”
Section: Expression Of Recombinant Hormonesmentioning
confidence: 99%